Effects of Poor Drainage Towards Road Functionality - Jonathan; Aulia Sari, Yusra; Andri Irfan Rifai (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
Batam City with existing drainage issues is a major hindrance to its performance. Road construction is always related to drainage funcitionality. The existing condition, with heavily piled-up sediments, causes a significant issue for Batam, Nagoya, and Batam Kota sub–district. Sediment accumulation in the drainage base depth causes a reduction in drainage volume, resulting in backflow and disturbance of water flow dynamics. This slowly erupts to the surface and cause flooding in roadways. Flooding roadways cause traffic congestion, erosion of the road structure, and accumulation of sediments due to the intensity of rainfall. Which resulting damages to drainage system. By installing sediment traps on manholes and lower base drainage, it can help reduce the buildup of sediments on the drainage base. Which will reduce flood risk and allow water to flow smoothly without resulting in backflow.